2016
DOI: 10.1186/s12915-016-0304-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Transcriptomic Analysis of a Beetle Chemosensory System Reveals a Gnathal Olfactory Center

Abstract: BackgroundThe red flour beetle Tribolium castaneum is an emerging insect model organism representing the largest insect order, Coleoptera, which encompasses several serious agricultural and forest pests. Despite the ecological and economic importance of beetles, most insect olfaction studies have so far focused on dipteran, lepidopteran, or hymenopteran systems.ResultsHere, we present the first detailed morphological description of a coleopteran olfactory pathway in combination with genome-wide expression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(161 citation statements)
references
References 240 publications
(335 reference statements)
17
144
0
Order By: Relevance
“…Difficult to characterize in synapsin or phalloidin stainings, backfills and antibody stainings against TKRP helped to identify numerous small glomeruli (Fig 4C–4G arrowheads) and to differentiate the AL from a structure which we identified as the lobus glomerulatus (LG) (Fig 4G), a deutocerebral structure typically found in hemimetabolous insects but recently also reported to occur in beetles [39]. In hemimetabolous insects, the LG has been described to receive first order gustatory and mechanosensory input from the mouthparts [71].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Difficult to characterize in synapsin or phalloidin stainings, backfills and antibody stainings against TKRP helped to identify numerous small glomeruli (Fig 4C–4G arrowheads) and to differentiate the AL from a structure which we identified as the lobus glomerulatus (LG) (Fig 4G), a deutocerebral structure typically found in hemimetabolous insects but recently also reported to occur in beetles [39]. In hemimetabolous insects, the LG has been described to receive first order gustatory and mechanosensory input from the mouthparts [71].…”
Section: Discussionmentioning
confidence: 99%
“…In hemimetabolous insects, the LG has been described to receive first order gustatory and mechanosensory input from the mouthparts [71]. A recent study in the beetle Tribolium castaneum suggested an innervation of the LG by OSNs based in sensilla of the mouthparts [39]. In all five investigated Coccinellidae, the ALs are remarkably small (Fig 1) and consist of numerous minute glomeruli (approximately 400–600 glomeruli per AL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-two Gr genes in the antennae and 69 Gr genes in mouthparts are highly expressed, and this species shows expression of many more types of Grs than other insect species [15]. This expanded Gr family likely plays a functional role for host selection.…”
Section: Introductionmentioning
confidence: 99%